2004
DOI: 10.1002/pbc.10482
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up of survivors of childhood cancer in the UK

Abstract: There are wide variations in the extent to which survivors of childhood cancer are discharged from hospital follow-up. There is a need for regularly updated national guidelines concerning the levels of follow-up required for specific groups of survivors defined principally by the treatment they received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 26 publications
0
54
0
11
Order By: Relevance
“…Of those, 93% exclusively involved a pediatric oncologist, 13% included a medical oncologist, and 8% included an adult-oriented primary care provider. In the United Kingdom, Taylor et al 51 surveyed 22 institutions and found that 52% of pediatric oncologists reported following up with their patients for life, whereas 45% discharge at least some for continued follow-up, usually with a general practitioner. In France, Tabone et al 52 conducted a survey of 40 pediatric oncologists in 28 centers.…”
Section: Current Practices In Transitional Carementioning
confidence: 99%
“…Of those, 93% exclusively involved a pediatric oncologist, 13% included a medical oncologist, and 8% included an adult-oriented primary care provider. In the United Kingdom, Taylor et al 51 surveyed 22 institutions and found that 52% of pediatric oncologists reported following up with their patients for life, whereas 45% discharge at least some for continued follow-up, usually with a general practitioner. In France, Tabone et al 52 conducted a survey of 40 pediatric oncologists in 28 centers.…”
Section: Current Practices In Transitional Carementioning
confidence: 99%
“…Survivors seen in long-term followup clinics have been found to be unrepresentative of the entire population of survivors. 27 This study also had the advantage of a representative range of childhood cancer types. Previous studies have had limited numbers of specific childhood cancer types, in particular numbers of leukemia survivors in older studies tend to be very limited.…”
Section: Study Strengths and Weaknessesmentioning
confidence: 99%
“…(21) Our results showed that similar to the UK and US, general practitioners were frequently involved in long-term care of childhood cancer survivors and saw the largest number of patients (n=164, 26%). (11,22) Thus, a follow-up model with general practitioners as gatekeepers transferring patients to specialists may cover best the needs of a majority of patients. However, preferences and views of survivors and physicians, as well as specific features of the health system need to be considered.…”
Section: Health Professionals Involved In Follow-upmentioning
confidence: 99%
“…Studies in the US, UK and Canada reported that contrary to recommendations, only one third of survivors received regular long-term follow-up. (11)(12)(13) In Switzerland and elsewhere, the implementation of follow-up programs for long-term survivors remains a challenge. The Swiss Paediatric Oncology Group (SPOG) has published recommendations for a standardized assessment of late effects in 1996 suggesting to involve medical oncologists and general practitioners to assure a seamless transition from paediatric to adult care.…”
Section: Introductionmentioning
confidence: 99%